Persistent Inequalities in Argentina in a Context of Economic Growth. A Feminist and Latin American Reading - Alonso, Virginia Noemí (Sociedad y Economía, 2022)
The article seeks to analyze gender inequality within the structure of private employment, affected by the phenomenon of structural heterogeneity during the period of economic growth between 2003 and 2013. To address this objective, a theoretical-methodological approach has been constructed through the dialogue of gender studies and feminist economics with the contributions of Latin American structuralism. The results of the research, which has applied a quantitative methodological strategy, show the existence of gender labor segregation anchored to the Argentine development style that limits the country’s ability to grow and develop with gender equality.